GRAFFITI TECHNIQUE DRAWING ACTIVITIES: IMPLICATIONS FOR CHILDREN'S CREATIVITY - Veryawan Veryawan; Ade Tursina (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2022)
Creativity is the ability to provide new ideas that can be applied in problem solving or as the ability to see new relationships between previously existing elements. There are many types of art activities that can stimulate the development of creativity in early childhood such as: playing with plasticine or playdough, finger painting (swab blur), printing, sewing, drawing, coloring, collage, finger painting, blowing color bubbles, painting with thread pulling techniques. , drawing with grafito techniques and so forth. In early childhood the development of art can be developed through drawing activities. Drawing is a basic form of art. Drawing activities can be done with the graffito technique. This research was conducted at RA Al-Ikhlas which is located at Jl. Gg Mosque. Meliala Rantau Utara, Labuhanbatu Regency. This study consisted of 2 cycles and started from 07 to 26 October 2019. The subjects of this study were students of RA Al - Ikhlas group B, totaling 15 people consisting of 7 men and 8 women with the theme being developed was plants. . This study uses a classroom action research (CAR) model which consists of 2 cycles. Each cycle is carried out according to the themes and factors studied. The procedure of this research is planning, implementation, action and reflection. In interpreting the results of the analysis carried out during the process of drawing activities with the grafito technique, the researcher used percentage analysis to obtain results about increasing the development of creativity in early childhood through the application of drawing activities with the grafito technique and analysis tests using the average child and the criteria for mastery learning of children.